Binder, negative pole piece, battery monomer, battery and electric device

By using the adhesive of the conductive network structure formed by polymer A and polymer B in lithium-ion batteries, the lithium-ion battery problem during fast charging is solved, and the fast charging performance and safety of the battery are improved.

CN119315030APending Publication Date: 2025-01-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310853214.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

During the fast charging process of lithium-ion batteries, due to excessive current, the negative electrode potential decreases, which increases the probability of lithium dendrites, and then lithium-ion evolution occurs, affecting the safety and energy density of the battery.

Method used

Using a binder containing polymer A and polymer B, polymer A is formed by copolymerization reaction of monomer I, monomer II and monomer III, which is hydrophilic and conductive, and polymer B is modified. Polyaniline forms a conductive network structure through intermolecular forces, improves the diffusion efficiency of lithium ions and reduces the probability of lithium evolution.

Benefits of technology

This binder improves the fast charging performance and safety of lithium-ion batteries by improving the diffusion efficiency of lithium ions and reducing the lithium-ion phenomenon, while maintaining the structural stability of the negative electrode material and reducing the generation of lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315030A_ABST
    Figure CN119315030A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a binder, a negative pole piece, a battery monomer, a battery and an electric device. The binder comprises a polymer A and a polymer B in a mass ratio of (14-18): (2-6), the polymer A is formed by polymerizing a monomer I, a monomer II and a monomer III, the polymer B comprises modified polyaniline, and the polymer A and the polymer B form the binder with a conductive network structure through intermolecular force. The binder has good flexibility, electrical conductivity, adhesion, hydrophilicity, chemical structure stability and the like, is beneficial for realizing the purpose of fast charging of the lithium ion battery, and relieves the problem of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a binder, a negative electrode sheet, a battery cell, a battery and an electrical device. Background Art

[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. Among them, lithium-ion batteries are widely used in portable electronic devices, electric vehicles and other fields. With the development of current society, people have higher and higher requirements for the fast charging performance of lithium-ion batteries.

[0003] However, the excessively high potential caused by fast charging and large current will cause the negative electrode potential to be too low, increasing the probability of lithium dendrites appearing at the negative electrode and leading to lithium deposition. Summary of the invention

[0004] In view of the above problems, the present application provides a binder, a negative electrode plate, a battery cell, a battery and an electrical device, which can improve the fast charging performance of lithium-ion batteries while reducing the probability of lithium plating.

[0005] In a first aspect, the present application provides a binder comprising a polymer A and a polymer B in a mass ratio of (14-18):(2-6);

[0006] The polymer A is formed by polymerizing monomer I, monomer II and monomer III; the polymer B comprises modified polyaniline;

[0007] The structural formula of the monomer I is shown in Formula I:

[0008]

[0009] Among them, R 11 Contains one of hydrogen and C1-C5 alkyl, and M contains one of hydrogen or alkali metal cation;

[0010] The structural formula of the monomer II is shown in Formula II:

[0011]

[0012] Among them, R 21 Contains one of hydrogen and C1-C5 alkyl;

[0013] The structural formula of the monomer III is shown in Formula III:

[0014]

[0015] Among them, R 31 Contains one of hydrogen and C1-C5 alkyl.

[0016] In the present application, each monomer constituting polymer A forms a linear prepolymer through a polymerization reaction, such as a copolymerization reaction: a monomer I-monomer II-monomer III copolymer, and the linear prepolymer has a hydrophilic polar group, such as a carboxyl group, an amide group, etc., and also has a weak polar group such as an alkyl group, which is conducive to achieving the hydrophilicity and strong polarity of the binder. The strong polarity has a strong adsorption effect on lithium ions, making it easy for lithium ions to conduct inside the binder; the monomers in the linear prepolymer, such as monomer II (including a cyano group), are conducive to achieving the chemical structure stability of the binder and further achieving its flexibility. The polymer B of the present application includes modified polyaniline, wherein polyaniline is a conductive polymer with good conductivity and electrochemical activity. The present application further mixes polymer A and polymer B together according to a certain amount, and the two form a binder with a conductive network structure through intermolecular forces. In the conductive network structure, polymer A and polymer B are uniformly dispersed, and polymer B is uniformly dispersed inside and outside the linear polymer A. The binder with a conductive network structure disclosed in the embodiment of the present application has good flexibility, conductivity, adhesion, hydrophilicity, and chemical structure stability. Among them, the binder contains polar groups that are conducive to the adsorption of lithium ions, and its good conductivity is also conducive to reducing resistance. Electrons and lithium ions can achieve stable conduction inside the binder, and the diffusion efficiency of lithium ions is improved by increasing diffusion channels and shortening diffusion distances. Lithium ions pass through the binder into the negative electrode sheet to receive electrons and complete lithium insertion. Since lithium ions are not easy to stack on the surface of the negative electrode sheet, the probability of forming a large number of lithium dendrites on the surface of the negative electrode sheet is reduced, and the occurrence of lithium precipitation is reduced. At the same time, the binder itself has good chemical structure stability, is not easy to be reduced even under low pressure conditions, and has little effect on the conduction of electrons and ions in the electrode. The good flexibility of the binder is conducive to ensuring that the negative active material does not fall off during repeated expansion and contraction. In addition, the binder has good adhesion, and it increases the binding force between itself, other additives, etc. and the negative active material to improve the structural stability of the negative material, which can reduce the peeling of the negative material itself and further reduce the probability of lithium dendrites.

[0017] In some embodiments of the present application, the mass ratio of polymer A to polymer B satisfies: (15-17): (2-6).

[0018] The polymer A and the polymer B of the present application can form a hydrophilic conductive network structure better within the mass ratio range.

[0019] In some embodiments of the present application, the mass ratio of polymer A to polymer B satisfies: (15-17): (3-5).

[0020] The hydrophilic conductive network formed by the polymer A and the polymer B of the present application within the mass ratio range is conducive to exerting its comprehensive properties such as flexibility, conductivity, adhesion, hydrophilicity, and chemical structure stability.

[0021] In some embodiments of the present application, the binder further comprises a solvent.

[0022] The polymer A and polymer B of the present application are dispersed in a solvent to form a uniformly dispersed system.

[0023] In some embodiments of the present application, the sum of the masses of the polymer A and the polymer B and the volume of the solvent satisfy: (1-10) kg / (80-100) L.

[0024] In the present application, the mixture formed by polymer A and polymer B is uniformly dispersed in a certain amount of solvent to form a binder, and the binder has a certain solid content at room temperature. The binder with a certain solid content has the advantages of good conductivity, strong adhesion, good chemical structure stability, etc.

[0025] In some embodiments of the present application, the solvent comprises water.

[0026] In the present application, since the mixture formed by polymer A and polymer B is hydrophilic, the selected solvent includes water to achieve environmental friendliness.

[0027] In some embodiments of the present application, the weight average molecular weight of the polymer A satisfies: 400,000 to 800,000.

[0028] In the present application, the weight average molecular weight is favorable for ensuring the flexibility and adhesion of polymer A.

[0029] In some embodiments of the present application, the weight average molecular weight of the polymer A satisfies: 440,000 to 765,000.

[0030] The polymer A in the present application has the weight average molecular weight, and can achieve uniform dispersion of the polymer B and facilitate the formation of a conductive network structure while ensuring its own excellent flexibility, adhesion and other characteristics.

[0031] In some embodiments of the present application, in monomer I, R 11 Contains one of hydrogen and C1-C3 alkyl.

[0032] In some embodiments of the present application, the monomer I comprises one or a combination of two or more of acrylic acid, methacrylic acid, ethacrylic acid, and lithium acrylate.

[0033] In some embodiments of the present application, the monomer II comprises one or both of acrylonitrile and methacrylonitrile.

[0034] In some embodiments of the present application, the monomer III comprises one or both of acrylamide and methacrylamide.

[0035] In some embodiments of the present application, based on the total weight of the polymer A, the mass percentage of the monomer I is 50% to 70%, the mass percentage of the monomer II is 20% to 30%, and the mass percentage of the monomer III is 10% to 20%.

[0036] The structure or properties of polymer A in the present application can be regulated according to the ratio between the monomers. The present application chooses to meet this ratio, which is beneficial to the hydrophilicity and flexibility of monomers I and III, and the chemical stability of monomer II, and ultimately realizes the hydrophilicity, flexibility and chemical structure stability of the binder.

[0037] In some embodiments of the present application, the weight average molecular weight of the polymer B satisfies: 50,000 to 60,000.

[0038] The polymer B in the present application has a weight average molecular weight that is conducive to ensuring the conductivity of the polymer B.

[0039] In some embodiments of the present application, the weight average molecular weight of the polymer B satisfies: 52450-59600.

[0040] The polymer B in the present application has such a weight average molecular weight, which is beneficial for it to exert its characteristic of conducting electrons in the binder while ensuring its own excellent conductivity.

[0041] In some embodiments of the present application, the polymer B comprises doped modified polyaniline.

[0042] In some embodiments of the present application, the doped modified polyaniline comprises modifying polyaniline with a dopant, and the dopant comprises one or more of polystyrene sulfonic acid, polystyrene sulfonate, polyvinyl sulfonic acid, and polyvinyl sulfonate.

[0043] After the polyaniline in the present application is modified by doping with a dopant, its conductivity is increased by more than ten orders of magnitude, so that the doped and modified polyaniline exhibits high conductivity.

[0044] In some embodiments of the present application, based on the total weight of the doped modified polyaniline, the mass percentage of the dopant is 5% to 20%.

[0045] The modification of polyaniline by the dopant in the present application includes an acid-base neutralization reaction process. By controlling the usage amount of the dopant and the polyaniline, it is beneficial to exert the high conductivity of the doped modified polyaniline.

[0046] In some embodiments of the present application, the performance of the binder at room temperature satisfies one or more of the following combinations:

[0047] (1) Solid content is 4% to 10%, preferably 4.5% to 9.8%;

[0048] (2) Viscosity is 10000 Pa·s to 20000 Pa·s, preferably 12500 Pa·s to 19750 Pa·s;

[0049] (3) The electrical conductivity is 5 S / cm to 20 S / cm, preferably 6.5 S / cm to 18.6 S / cm.

[0050] The second aspect of the present application is to provide a negative electrode plate, which includes a negative electrode collector and a negative electrode membrane arranged on at least one surface of the negative electrode collector, and the negative electrode membrane includes a negative electrode active material, a conductive agent, a dispersant and the binder described in the first aspect.

[0051] In some embodiments of the present application, based on the total weight of the negative electrode film, the binder has a content of 1.5% to 3.0% by mass, preferably 1.8% to 2.5% by mass.

[0052] In some embodiments of the present application, based on the total weight of the negative electrode film, the mass percentage content of the conductive agent is 0.2% to 2.0%.

[0053] In some embodiments of the present application, based on the total weight of the negative electrode film, the mass percentage content of the conductive agent is 0.2% to 1.5%.

[0054] In some embodiments of the present application, based on the total weight of the negative electrode film, the mass percentage content of the conductive agent is 0.2% to 0.5%.

[0055] In some embodiments of the present application, based on the total weight of the negative electrode membrane, the mass percentage content of the dispersant is 0.2% to 2.0%.

[0056] In some embodiments of the present application, based on the total weight of the negative electrode membrane, the mass percentage content of the dispersant is 0.2% to 1.5%.

[0057] In some embodiments of the present application, based on the total weight of the negative electrode membrane, the mass percentage content of the dispersant is 0.2% to 0.9%.

[0058] The third aspect of the present application is to provide a battery cell comprising the negative electrode plate described in the second aspect.

[0059] The fourth aspect of the present application is to provide a battery, comprising the battery cell described in the third aspect.

[0060] The fifth aspect of the present application is to provide an electrical device, comprising the binder described in the first aspect or the negative electrode plate described in the second aspect or the battery cell described in the third aspect or the battery described in the fourth aspect.

[0061] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Also, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0063] Figure 1 A schematic diagram of battery dynamics for some embodiments of the present application;

[0064] Figure 2 Schematic diagram of the adhesive structure of some embodiments of the present application;

[0065] Figure 3 A schematic diagram of the structure of a vehicle according to some embodiments of the present application;

[0066] Figure 4 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;

[0067] Figure 5 A diagram of battery lithium deposition in some embodiments of the present application;

[0068] The reference numerals in the specific implementation manner are as follows:

[0069] 10000, vehicles;

[0070] 1000, battery; 2000, controller; 3000, motor;

[0071] 100. Single cell;

[0072] 200, box body; 210, first part; 220, second part;

[0073] 20000, adhesive;

[0074] 2100, polymer A; 2200, polymer B. DETAILED DESCRIPTION

[0075] Hereinafter, the embodiments of the binder, negative electrode sheet, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0076] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0077] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0078] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0079] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0080] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0081] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0082] Summary of the main line of invention:

[0083] With the development of society, people have higher and higher requirements for the fast charging performance of lithium-ion batteries. One of the factors affecting the fast charging performance of lithium-ion batteries is the negative electrode. When the lithium-ion battery is charging, the lithium ions migrate from the positive electrode to the negative electrode. The excessive potential caused by the large current of fast charging will cause the negative electrode potential to be more negative. At this time, the pressure on the negative electrode to quickly accept lithium will increase, and the tendency to generate lithium dendrites will also increase. Therefore, during fast charging, the negative electrode must not only meet the kinetic requirements of lithium diffusion, but also face the safety problems caused by the increased tendency of lithium dendrite generation.

[0084] In order to solve the above problems, the prior art describes a method of optimizing the negative electrode material to improve its own structural stability and promote the diffusion of lithium ions. However, this method has the disadvantages of reduced battery energy density, more complicated process and increased cost.

[0085] Existing negative electrode binders such as styrene-butadiene rubber and sodium carboxymethyl cellulose have poor electronic and ionic conductivity, and swell to a certain extent in the electrolyte. They cannot guarantee efficient electron transfer in the electrode, and cannot meet the kinetic requirements of lithium diffusion, nor can they alleviate the lithium precipitation phenomenon caused by lithium dendrites. If a binder that meets the kinetic requirements of lithium diffusion can be provided, it is not easy to be reduced at the low potential caused by fast charging and large current, and does not swell in the electrolyte or has a small swelling coefficient, it will be beneficial to achieve the fast charging performance of lithium-ion batteries.

[0086] Based on the above considerations, in order to solve the problem of increased probability of negative electrode lithium dendrites and subsequent obvious lithium plating during fast charging of lithium-ion batteries, the applicant obtained a binder, a negative electrode sheet, a battery cell, a battery and an electrical device based on the above design concept and relevant experimental research.

[0087] First, the binder comprises a polymer A and a polymer B in a mass ratio of (14-18):(2-6), wherein the polymer A is formed by polymerizing a monomer I, a monomer II and a monomer III; the polymer B comprises modified polyaniline; the structural formula of the monomer I is as shown in formula I, wherein R 11 Contains one of hydrogen and C1-C5 alkyl, and M contains any one of hydrogen or alkali metal cation;

[0088]

[0089] The structural formula of monomer II is shown in Formula II, wherein R 21 Contains one of hydrogen and C1-C5 alkyl;

[0090]

[0091] The structural formula of monomer III is shown in formula III, wherein R 31 Contains one of hydrogen and C1-C5 alkyl;

[0092]

[0093] The polymer A of the present application is a linear polymer, and the polymer B has conductivity. The two form a binder through intermolecular forces, such as van der Waals forces and hydrogen bonds. In the binder, polymer A is uniformly dispersed in a linear form, and polymer B is uniformly dispersed inside and outside the linear polymer A and interpenetrates to form a conductive network structure. Since polymer A itself also has hydrophilic and other polar groups, such as carboxyl groups, amide groups, etc., it has a certain hydrophilicity, and polymer B can provide electron transfer function, and finally a binder with a hydrophilic conductive network structure is formed.

[0094] The binder with a hydrophilic conductive network structure disclosed in the embodiment of the present application has good flexibility, conductivity, adhesion, hydrophilicity, and chemical structure stability, which is conducive to achieving the purpose of fast charging of lithium-ion batteries and alleviating the problem of lithium dendrites. The charging process of lithium-ion batteries includes the following principles, which can also be specifically combined with the drawings in the specification Figure 1 For detailed explanation:

[0095] a. When a lithium-ion battery begins to charge, the current provided by the external power source or charger passes through the circuit between the positive and negative electrodes of the battery, which causes the lithium ions in the positive electrode sheet to be oxidized and detach from the lattice structure of the positive electrode material. At the same time, the electrons in the positive electrode material flow through the external circuit and enter the negative electrode of the battery.

[0096] b. Lithium ions are released from the positive electrode and enter the electrolyte to form solvated lithium ions, which then move from the positive electrode to the negative electrode through the solvated lithium ions.

[0097] c. Solvated lithium ions and external circuit electrons pass through the binder or dispersant on the surface of the negative electrode active material, and then enter the surface of the negative electrode active material, and the interfacial charge transfer process occurs on the surface of the SEI film. The interfacial charge transfer includes four steps: ①Li + The solvated complex desolvates on the surface of the SEI film; ②Li + Diffusion mass transfer in the SEI membrane; ③ Charge reaction occurs at the SEI / graphite interface to form (e, Li + ) electric pair; ④(e, Li + )The electric pairs enter and transfer to the negative electrode active material phase.

[0098] like Figure 1 As shown in A, conventional binders, such as SBR and CMC systems, do not conduct lithium ions or electrons, which reduces the rate at which lithium ions and electrons enter the surface of the negative electrode active material; Figure 1As shown in Figure B, the binder with a hydrophilic conductive network structure provided by the present application contains polar groups that are conducive to the adsorption of lithium ions. On the other hand, the good conductivity of the binder itself is conducive to reducing resistance, and electrons and lithium ions can be stably connected inside the binder. The diffusion efficiency of lithium ions is improved by increasing the diffusion channel and shortening the diffusion distance. Lithium ions pass through the binder into the negative electrode active material to receive electrons and complete lithium insertion. Since lithium ions are not easy to stack on the surface of the negative electrode plate, the probability of depositing a large number of lithium dendrites on the surface of the negative electrode plate is reduced, and the occurrence of lithium precipitation is reduced. At the same time, the chemical structure stability of the binder itself is good, and it is not easy to be reduced even under low pressure conditions, and the conduction of electrons and ions in the electrode is small. The good flexibility of the binder is conducive to ensuring that the negative electrode active material does not fall off during repeated expansion and contraction. In addition, the binder has good adhesion, and it increases the binding force between itself and other additives and negative electrode active materials to improve the structural stability of the negative electrode material, which can reduce the peeling of the negative electrode material itself and further reduce the probability of lithium dendrites. Therefore, the binder provided by the present application is ultimately conducive to improving the kinetic properties of the battery and alleviating the safety problems caused by lithium dendrites.

[0099] The binder disclosed in the embodiment of the present application can be mixed with the negative electrode active material, the conductive agent, the dispersant, etc. and then arranged on at least one surface of the negative electrode current collector to form a negative electrode membrane, and finally obtain a negative electrode sheet. Among the components of the negative electrode membrane, firstly, since the binder of the present application has a certain conductivity, it can itself act as a part of the conductive agent, which can reduce the amount of conductive agent used. Secondly, it has good adhesion, and can reduce its own usage without affecting the adhesion performance. In addition, the binder has the characteristics of flexibility, hydrophilicity, and chemical structure stability. It can achieve the purpose of uniformly dispersing the negative electrode active material in the negative electrode membrane, such as suspending the negative electrode active material, further reducing the amount of dispersant used. Based on the total weight of the components of the negative electrode membrane, the amount of conductive agent and dispersant used is reduced, which will inevitably lead to an increase in the amount of negative electrode active material used, so it is beneficial to increase the energy density of the negative electrode sheet.

[0100] The negative electrode sheet disclosed in the embodiment of the present application can be combined with the positive electrode sheet, the separator, the electrolyte, etc. to form a battery cell using any conventional process in the art. Multiple battery cells form a battery, which can be used in but not limited to electric devices such as vehicles, ships or aircraft; further, the electric device is applied to the power supply system to achieve the purpose of fast charging and reduce the probability of lithium dendrites.

[0101] The embodiment of the present application provides an electric device using a battery as a power source. The electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, for example, a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0102] Binder

[0103] According to some embodiments of the present application, the present application provides a binder, which comprises a polymer A and a polymer B in a mass ratio of (14-18):(2-6); wherein polymer A is formed by polymerization of the following monomers I, II and III, wherein the structural formula of monomer I is shown in formula I, the structural formula of monomer II is shown in formula II, and the structural formula of monomer III is shown in formula III:

[0104]

[0105] In Formula I, R 11 Contains one of hydrogen and C1-C5 alkyl, M contains any one of hydrogen or alkali metal cation; In formula II, R 21 Contains one of hydrogen and C1-C5 alkyl; in Formula III, R 31 Contains one of hydrogen and C1-C5 alkyl; and polymer B contains modified polyaniline.

[0106] The binder of the present application includes any conventional meaning in the art, and is mainly used to achieve bonding between the components in the negative electrode membrane. The binder mainly includes polymer A and polymer B, and the polymer also includes any conventional meaning in the art, for example, polymer A is formed by covalently connecting monomer I, monomer II and monomer III, and polymer B is formed by covalently connecting aniline and a modifier for modifying aniline, and the modification and the modifier include any conventional meaning in the art, such as physically, chemically or otherwise changing aniline to improve the performance of aniline or polyaniline. The functional group C1-C5 alkyl may include methyl, ethyl, propyl, butyl, pentyl and isomers thereof, and the alkali metal cation may include lithium ions, sodium ions, potassium ions, etc.

[0107] The monomers constituting polymer A of the present application form a linear prepolymer through a polymerization reaction, such as a copolymerization reaction: a copolymer of monomer I-monomer II-monomer III. The linear prepolymer has hydrophilic polar groups, such as carboxyl groups, amide groups, etc., and also has weak polar groups such as alkyl groups, which are beneficial to achieving the hydrophilicity and strong polarity of the binder. The strong polarity has a strong adsorption effect on lithium ions, making it easy for lithium ions to conduct inside the binder. Monomers in the linear prepolymer, such as monomer II (containing cyano groups), are beneficial to achieving the chemical structure stability of the binder and further achieving its flexibility. The polymer B of the present application contains modified polyaniline, wherein polyaniline is a conductive polymer with good conductivity and electrochemical activity. The present application further mixes polymer A and polymer B together in a certain amount, and the two form a binder with a hydrophilic conductive network structure through intermolecular forces. Such as Figure 2 As shown, polymer A and polymer B interpenetrate to form a conductive network structure, in which polymer A and polymer B are uniformly dispersed, and polymer B is uniformly dispersed inside and outside the linear polymer A. The binder with a hydrophilic conductive network structure disclosed in the embodiment of the present application has good flexibility, conductivity, adhesion, hydrophilicity, and chemical structure stability. Among them, the binder contains polar groups that are conducive to the adsorption of lithium ions, and its good conductivity is also conducive to reducing resistance. Electrons and lithium ions can achieve stable conduction inside the binder, and the diffusion efficiency of lithium ions can be improved by increasing diffusion channels and shortening diffusion distances. Lithium ions pass through the binder into the negative electrode sheet to receive electrons and complete lithium insertion. Since lithium ions are not easy to stack on the surface of the negative electrode sheet, the probability of forming a large number of lithium dendrites on the surface of the negative electrode sheet is reduced, and the occurrence of lithium precipitation is reduced. At the same time, the binder itself has good chemical structure stability, is not easy to be reduced even under low pressure conditions, and has little effect on the conduction of electrons and ions in the electrode. The good flexibility of the binder is conducive to ensuring that the negative active material does not fall off during repeated expansion and contraction. In addition, the binder has good adhesion, and it improves the structural stability of the negative electrode material by increasing the binding force between itself, other additives, etc. and the negative electrode active material, which can reduce the peeling of the negative electrode material itself and further reduce the probability of lithium dendrites.

[0108] According to some embodiments of the present application, the mass ratio of polymer A to polymer B satisfies: (15-17): (2-6). Within this mass ratio range, the two can better form a hydrophilic conductive network structure.

[0109] According to some embodiments of the present application, the mass ratio of polymer A to polymer B satisfies: (15-17): (3-5). Within this mass ratio range, the formed hydrophilic conductive network is conducive to exerting its comprehensive properties such as flexibility, conductivity, adhesion, hydrophilicity, and chemical structure stability.

[0110] According to some embodiments of the present application, the binder further includes a solvent; since the mixture formed by polymer A and polymer B is hydrophilic, polymer A and polymer B are dispersed in the solvent to form a uniformly dispersed system, that is, a solvent such as water is conducive to further dispersion of the mixture formed by polymer A and polymer B, and the water here includes but is not limited to deionized water.

[0111] According to some embodiments of the present application, when the total mass of polymer A and polymer B and the volume of the solvent are controlled to satisfy: (1-10) kg / (80-100) L, the mixture formed by polymer A and polymer B is evenly dispersed in the solvent to form a binder, and the binder has a certain solid content at room temperature. The binder with a certain solid content has the advantages of good conductivity, strong adhesion, good chemical structure stability, etc.

[0112] According to some embodiments of the present application, the solid content of the binder at room temperature is 4% to 10%.

[0113] The solid content in this application includes any meaning of conventional binders in the field, including the ratio of the mass of solid matter in the binder to the total mass. The solid content test method includes any conventional form in the field, such as drying method, combustion method, etc. This application chooses to use the drying method to measure the specific value of the solid content. At this solid content, it is conducive to the bonding of the binder to other components in the negative electrode membrane.

[0114] According to some embodiments of the present application, the solid content of the binder at room temperature is 4.5% to 9.8%.

[0115] The binder in the present application has this solid content, which is conducive to achieving stronger and longer-lasting adhesion to other components in the negative electrode plate.

[0116] According to some embodiments of the present application, the viscosity of the adhesive at room temperature is 10000 Pa·s to 20000 Pa·s.

[0117] The viscosity in the present application mainly includes any content conventional in the art, and its value is related to the interaction force between components. The measurement method can include direct measurement using conventional measuring instruments, such as a viscometer, a rotational rheometer, etc.

[0118] According to some embodiments of the present application, the viscosity of the adhesive at room temperature is 12500 Pa·s to 19750 Pa·s.

[0119] The binder in the present application has such viscosity, which is beneficial to the subsequent preparation of the negative electrode sheet and the realization of stronger and longer-lasting adhesion to other components in the negative electrode sheet.

[0120] According to some embodiments of the present application, the electrical conductivity of the binder at room temperature is 5 S / cm to 20 S / cm.

[0121] The conductivity in this application includes any conventional meaning in the art, which includes the ability of the binder to transfer electrons and conduct current. The test method of conductivity includes any conventional form in the art, such as using an instrument for measuring conductivity, such as direct measurement with a conductivity meter or other methods. Under this conductivity, the binder itself has low resistance and better conductivity.

[0122] According to some embodiments of the present application, the electrical conductivity of the binder at room temperature is 6.5 S / cm to 18.6 S / cm.

[0123] The binder in the present application has such electrical conductivity, which is conducive to achieving good conduction of electrons inside the binder.

[0124] According to some embodiments of the present application, the weight average molecular weight of polymer A satisfies: 400,000 to 800,000.

[0125] The weight average molecular weight in this application includes any meaning in the art, wherein the weight average molecular weight can be obtained by calculation, or can be directly measured by experimental techniques such as gel permeation chromatography (GPC) or physical methods such as light scattering. At this weight average molecular weight, it is beneficial to ensure the linearity and hydrophilicity of polymer A itself.

[0126] According to some embodiments of the present application, the weight average molecular weight of polymer A satisfies: 440,000 to 765,000.

[0127] The polymer A in the present application has the weight average molecular weight, which ensures that it has excellent properties such as linearity and hydrophilicity, and is also conducive to uniform dispersion in the solvent and further dispersion of the polymer B.

[0128] According to some embodiments of the present application, in monomer I, R 11 Contains one of hydrogen and C1-C3 alkyl.

[0129] The monomer I in the present application contains both polar groups such as carboxyl groups, ester groups, etc. and non-polar groups such as alkyl groups. If the alkyl group has a large molecular weight or is branched, it is actually not conducive to the formation of a flexible and hydrophilic polymer A. Therefore, the present application selects a short-chain alkyl group, and further selects the monomer I to contain one or a combination of more than two of acrylic acid, methacrylic acid, ethacrylic acid, and lithium acrylate; if the monomer I contains lithium acrylate, its own high ionic conductivity is conducive to further optimizing the conductivity of the polymer A.

[0130] According to some embodiments of the present application, monomer II includes one or both of acrylonitrile and methacrylonitrile.

[0131] According to some embodiments of the present application, monomer III comprises one or both of acrylamide and methacrylamide.

[0132] As the alkyl carbon chain of monomer II and monomer III in the present application increases, their reactivity in copolymerization with monomer I or with each other decreases, and it is not conducive to the formation of linear prepolymers, so short-chain alkyl is selected in the present application.

[0133] According to some embodiments of the present application, based on the total weight of polymer A, the mass percentage of monomer I is 50% to 70%, the mass percentage of monomer II is 20% to 30%, and the mass percentage of monomer III is 10% to 20%.

[0134] Among them, monomer I, monomer II and monomer III are copolymerized to obtain polymer A (linear prepolymer). The structure or properties of polymer A can be regulated according to the ratio between the monomers. The present application chooses to meet this ratio, which is beneficial to the hydrophilicity and flexibility of monomer I and monomer III, and the chemical stability of monomer II, and finally realizes the hydrophilicity, flexibility and chemical structure stability of the binder.

[0135] According to some embodiments of the present application, the copolymerization reaction between monomer I, monomer II and monomer III comprises any conventional reaction in the art, such as placing monomer I, monomer II and monomer III having a certain amount ratio of substances in a reaction container, adding a solvent such as ethanol and stirring and mixing them thoroughly to obtain a monomer solution C with a certain concentration, and then adding a required amount of chain transfer agent to the monomer solution C, stirring and mixing, and heating to 50-100° C. to obtain a mixed solution D; taking the required amount of initiator for the reaction and dissolving it in a solvent such as water to form an aqueous solution E containing the initiator, and adding the aqueous solution E containing the initiator dropwise to the mixed solution D. After the dropwise addition is completed, reacting at 50-100° C. for 5-8 hours to prepare a mixed system F containing monomer I, monomer II and monomer III; adding the required amount of chain terminator for the reaction to the mixed system F containing monomer I, monomer II and monomer III, and adjusting the pH of the system to 7-10 at the same time, continuing the reaction for 10-30 minutes, then stopping heating, and cooling under stirring to obtain a mixed solution J containing polymer A. The chain transfer agent, initiator, chain terminator, etc. used in the copolymerization reaction include any conventional types in the art, for example, the chain transfer agent includes but is not limited to one or more combinations of sodium sulfite, sodium hypophosphite, sodium bisulfite, sodium formate, mercaptopropanol and mercaptoacetic acid; the initiator may include but is not limited to one or more combinations of ammonium persulfate, potassium persulfate, hydrogen peroxide, sodium persulfate and azobisisobutyronitrile; the chain terminator may include but is not limited to one or more combinations of sodium sulfite, sodium hypophosphite and sodium bisulfite; in addition, the solution used to adjust the pH includes an alkaline solution, such as sodium hydroxide, potassium hydroxide or ammonia water.

[0136] According to some embodiments of the present application, the weight average molecular weight of polymer B satisfies: 50,000 to 60,000. The weight average molecular weight in the present application includes any meaning in the art, as described above, wherein the weight average molecular weight can be obtained by calculation, or it can be directly measured using experimental techniques such as gel permeation chromatography (GPC) or physical methods such as light scattering. At this weight average molecular weight, it is beneficial to ensure the conductivity of polymer B.

[0137] According to some embodiments of the present application, the weight average molecular weight of polymer B satisfies: 52450-59600.

[0138] The polymer B in the present application has such a weight average molecular weight, which is beneficial for it to exert its characteristic of conducting electrons in the binder while ensuring its own excellent conductivity.

[0139] According to some embodiments of the present application, polymer B includes doped modified polyaniline.

[0140] The doping in this application includes any conventional doping in the art, such as physical doping or chemical doping with reagents. This application includes modifying polyaniline with a dopant, and the dopant includes one or more of polystyrene sulfonic acid, polystyrene sulfonate, polyvinyl sulfonic acid, and polyvinyl sulfonate. After polyaniline is modified by doping with a dopant, its conductivity is increased by more than ten orders of magnitude, so that the doped modified polyaniline exhibits high conductivity.

[0141] According to some embodiments of the present application, based on the total weight of the doped modified polyaniline, the mass percentage of the dopant is 5% to 20%.

[0142] The modification of polyaniline by the dopant in the present application includes an acid-base neutralization reaction process. By controlling the usage amount of the dopant and the polyaniline, it is beneficial to exert the high conductivity of the doped modified polyaniline.

[0143] According to some embodiments of the present application, the acid-base neutralization reaction process between the dopant and polyaniline includes a chemical oxidation polymerization reaction between the reaction raw materials such as aniline monomer and the dopant, specifically, a certain amount of dopant is diluted in a solvent such as water, aniline monomer is added under stirring conditions, and a mixture is formed after mixing, and an acidic solution of the oxidant is added dropwise to the mixture under vigorous stirring, and then transferred to an ice bath such as 0-5°C and stirred at a constant temperature for about 12 hours, and an equal volume of solvent such as acetone is poured into the reaction solution, and polymer B is obtained by impurity removal and drying, and polymer B is in a solid state. The oxidant used in the chemical oxidation polymerization reaction includes any conventional type in the art, such as ammonium persulfate, etc., and the acidic solution includes an aqueous solution of hydrogen chloride.

[0144] Battery Cell

[0145] [Negative electrode]

[0146] The binder disclosed in the embodiment of the present application can be mixed with the negative electrode active material, the conductive agent, the dispersant, etc. and then arranged on at least one surface of the negative electrode current collector to form a negative electrode membrane, and finally obtain a negative electrode sheet. Among the components of the negative electrode membrane, firstly, since the binder of the present application has a certain conductivity, it can itself act as a part of the conductive agent, which can reduce the amount of conductive agent used. Secondly, it has good adhesion and can reduce its own usage without affecting the adhesion performance. In addition, the binder has the characteristics of flexibility, hydrophilicity, and chemical structure stability. It can achieve the purpose of uniformly dispersing the negative electrode active material in the negative electrode membrane, such as suspending the negative electrode active material, further reducing the amount of dispersant used. Based on the total weight of the components of the negative electrode membrane, the reduction in the amount of conductive agent and dispersant used will inevitably lead to an increase in the amount of negative electrode active material used, so it is beneficial to increase the energy density of the negative electrode sheet.

[0147] According to some embodiments of the present application, based on the total weight of the negative electrode film, the binder has a content of 1.5% to 3.0% by mass.

[0148] In the present application, when the binder content is lower than 1.5%, it is not conducive to exerting its conductivity, adhesion, etc. When its content is higher than 3.0%, it is easy to affect the proportion of negative electrode active material. Therefore, the present application selects its content to be between 1.5% and 3.0%.

[0149] According to some embodiments of the present application, based on the total weight of the negative electrode film, the mass percentage content of the binder is 1.8% to 2.5%.

[0150] In the present application, when the content of the binder is between 1.8% and 2.5%, it is beneficial to exert its own conductivity and adhesion, and will not affect the proportion of the negative electrode active material.

[0151] According to some embodiments of the present application, based on the total weight of the negative electrode film, the mass percentage content of the binder is 2.0%. The present application focuses on exploring the dynamic performance of the battery under this percentage of the binder.

[0152] According to some embodiments of the present application, based on the total mass of the negative electrode film, the mass percentage content of the conductive agent is 0.2% to 2.0%.

[0153] In the present application, since the binder is conductive, it can reduce the amount of conductive agent used. For example, the conductive agent conventionally used in the negative electrode plate in the art can account for as high as 3.0% or more. By reducing the amount of conductive agent used, the present application can indirectly increase the amount of negative electrode active material used, thereby improving the battery energy density.

[0154] According to some embodiments of the present application, based on the total weight of the negative electrode film, the mass percentage content of the conductive agent is 0.2% to 1.5%.

[0155] The conductive agent of the present application, at this proportion, does not affect the conductive function that the conductive agent should play in the negative electrode plate, and can also increase the usage of negative electrode active material and improve the battery energy density.

[0156] According to some embodiments of the present application, based on the total weight of the negative electrode membrane, the mass percentage content of the dispersant is 0.2% to 2.0%.

[0157] The binder in the present application is a hydrophilic conductive network structure, which can achieve uniform dispersion of the negative electrode activity, that is, it has a dispersing function, so it can replace part of the dispersant and then indirectly increase the amount of negative electrode active material used by reducing the amount of dispersant used, ultimately achieving the technical purpose of increasing the battery energy density.

[0158] According to some embodiments of the present application, based on the total weight of the negative electrode membrane, the mass percentage content of the dispersant is 0.2% to 1.5%.

[0159] The dispersant of the present application, at this ratio, does not affect the dispersing function that the dispersant should perform in the negative electrode plate, and can also increase the usage of negative electrode active material and improve the battery energy density.

[0160] The conductive agent in the present application includes any conventional type in the art, such as one or a combination of two or more of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers; the dispersant in the present application also includes any conventional type in the art, such as cellulose and its salts, specifically including but not limited to methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, etc.

[0161] The negative electrode active material in the present application includes a carbonaceous material, and the carbonaceous material includes one or a combination of two or more of artificial graphite, natural graphite, soft carbon, and hard carbon. Among them, artificial graphite, natural graphite, soft carbon, hard carbon, etc. include materials of any form conventional in the art, and include any conventional manufacturers and models in the art. At the same time, the negative electrode active material may also include a silicon-based material, and the silicon-based material includes one or two of a silicon-oxygen material or a silicon-carbon material. In addition, the negative electrode active material may also include a silicon-carbon composite, a Li-Sn alloy, a Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 , Li-Al alloy. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for lithium-ion batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0162] The negative electrode current collector in the present application may be a metal foil or a composite current collector, the metal foil may be a copper foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.

[0163] [Positive electrode]

[0164] The positive electrode sheet in the present application includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material, a positive electrode conductive agent, a positive electrode binder, etc. The present application does not specifically limit the specific type of the positive electrode active material. For example, when the positive electrode sheet is used in a lithium-ion battery, the positive electrode active material includes but is not limited to LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM111) 、 LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523) 、LiNi 0.6 CO 0.2 Mn 0.2 O2(NCM622) 、 LiNi 0.8 CO 0.1 Mn 0.1 O2(NCM811) 、LiNi 0.85 CO 0.15 Al 0.05 O2, LiFePO4 (LFP) and LiMnPO4. One or more of the following. The positive electrode conductive agent includes but is not limited to one or more combinations of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers. The positive electrode binder includes but is not limited to polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, carboxymethyl chitosan, etc. One or more combinations. The positive electrode current collector in the present application can be a metal foil or a composite current collector, wherein the metal foil can be an aluminum foil, and the composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming metal materials such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0165] [Electrolyte]

[0166] The electrolyte in the present application is used to achieve ion conduction between the positive electrode plate and the negative electrode plate. The electrolyte includes an electrolyte salt and a solvent, wherein the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate. The solvent may include at least one selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone or an ether solvent such as triethylene glycol dimethyl ether.

[0167] [Isolation film]

[0168] In the present application, the separator between the positive electrode and the negative electrode can be any known porous structure separator with good chemical stability and mechanical stability. For example, the material of the separator may include but is not limited to one or a combination of two or more of the following groups: glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film without special restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different without special restrictions.

[0169] [Electrical devices]

[0170] For the convenience of explanation, some embodiments of the present application are described by taking a vehicle as an example of an electrical device.

[0171] Please refer to Figure 3 , Figure 3 A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.

[0172] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.

[0173] Please refer to Figure 4 , Figure 4 The exploded diagram of the battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a single cell 100. Conventional single cells include primary cells or secondary cells. The present application specifically protects secondary cells. The single cell 100 is contained in the housing 200. The housing 200 is used to provide a containing space for the single cell 100. The housing 200 can adopt a variety of structures.

[0174] In some embodiments, the box body 200 may include a first part 210 and a second part 220, the first part 210 and the second part 220 cover each other, and the first part 210 and the second part 220 jointly define a storage space for accommodating the secondary battery 100. The second part 220 may be a hollow structure with one end open, and the first part 210 may be a plate-like structure, and the first part 210 covers the open side of the second part 220, so that the first part 210 and the second part 220 jointly define a storage space; the first part 210 and the second part 220 may also be hollow structures with one side open, and the open side of the first part 210 covers the open side of the second part 220. Of course, the box body 200 formed by the first part 210 and the second part 220 may be in various shapes, such as a cylinder, a cuboid, etc.

[0175] In the battery 1000, there may be multiple single cells 100, and the multiple single cells 100 may be connected in series, in parallel, or in mixed connection. Mixed connection means that the multiple single cells 100 are both connected in series and in parallel. The multiple single cells 100 may be directly connected in series, in parallel, or in mixed connection, and then the whole formed by the multiple single cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple single cells 100 in series, in parallel, or in mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in mixed connection to form a whole, and then accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a busbar component for realizing electrical connection between the multiple single cells 100.

[0176] The single cell 100 may be a lithium-ion battery, a sodium-ion battery or other batteries, and the single cell 100 may be cylindrical, flat, rectangular or in other shapes.

[0177] [Preparation of Binder]

[0178] According to some embodiments of the present application, the preparation method of the binder is as follows:

[0179] (1) Preparation of polymer B:

[0180] 7.5 g of polystyrene sulfonic acid aqueous solution (30 wt%) was diluted in 20 mL of deionized water, 0.2 g of aniline monomer was dropped into the above solution under stirring and kept for 30 minutes to form a mixture, then, under vigorous stirring, an aqueous solution of ammonium persulfate in hydrogen chloride was dropped into the above mixture, after the dropwise addition was completed, the mixture was transferred to an ice bath (0-5° C.) and stirred at constant temperature for 12 hours, the aqueous solution of ammonium persulfate in hydrogen chloride was formed by dispersing 0.5 g of ammonium persulfate in a 2M aqueous solution of hydrogen chloride. An equal volume of acetone was poured into the mixed solution, and then the mixture was filtered and washed three times with acetone and deionized water respectively to remove impurities such as oxidant ammonium persulfate or aniline monomer, and then vacuum dried at 40° C. for 48 hours, and the solid was collected and ground into fine powder to obtain polymer B.

[0181] (2) Prepare polymer A, the preparation method of polymer A is as follows:

[0182] (2.1) Adding three monomers, acrylic acid, acrylonitrile and acrylamide, in a ratio of 50%:30%:20% by mass into a reaction vessel, adding ethanol and stirring to completely dissolve the monomers, and obtaining a monomer solution C with a total concentration of 20% to 80%;

[0183] (2.2) 2 to 10 parts by weight of a chain transfer agent are added to a monomer solution C, stirred to fully dissolve, and heated to 50 to 100° C. to obtain a mixed solution D; 1 to 30 parts by weight of an initiator are dissolved in water to form an aqueous solution E containing the initiator (with a concentration of 20% to 80%), and the aqueous solution E containing the initiator is then added dropwise to the mixed solution D. After the addition is completed, the mixture is reacted at 50 to 100° C. for 5 to 8 hours to prepare a mixed system F containing acrylic acid-acrylamide copolymer-acrylonitrile;

[0184] (2.3) Add 2 to 30 parts by weight of a chain terminator to the mixed system F, and simultaneously add an alkaline solution to adjust the pH to 7 to 10. After reacting for 10 to 30 minutes, stop heating, and cool under stirring to obtain a mixed solution J containing polymer A.

[0185] (3) Preparation of binder:

[0186] The polymer B prepared in step (1) is dispersed in deionized water and stirred for about 12 hours to form a mixed solution containing polymer B, and then the mixed solution J containing polymer A prepared in step (2) is fully mixed with the mixed solution containing polymer B to form a binder, wherein the mass ratio of polymer A to polymer B is (14-18):(2-6), and the total mass of polymer A and polymer B and the volume of solvent deionized water satisfy: (1-10) kg / (80-100) L; the solid content of the binder at room temperature is 4%-10%, the viscosity is 10000 Pa·s-20000 Pa·s, and the conductivity is 5S / cm-20S / cm.

[0187] Embodiments 1 to 20 provide a binder, a negative electrode plate and a battery, wherein the polymer B contained in the binder has a dopant content of 5% to 20% by weight based on the total weight of the doped modified polyaniline;

[0188] Among them, Examples 1 to 9 are prepared according to the above-mentioned binder preparation method, and the mass percentage of the dopant is about 10% based on the total weight of the doped modified polyaniline; the remaining examples are binders formed by adjusting the monomer dosage, reaction conditions, etc.

[0189] Comparative Example 1 provides the use of SBR (Japan Zeon) as a binder applied to the negative electrode plate, Comparative Example 2 provides the use of CMC (Changshu Weiyi) as a binder applied to the negative electrode plate, Comparative Examples 3, 4, 5 and 6 use different types of monomers to prepare the binder or use polymer A and polymer B with different ratios to form the binder.

[0190] The specific parameters and performance characteristics of the binder are shown in Table 1:

[0191] Table 1 Parameters of adhesives

[0192]

[0193]

[0194] [Preparation of negative electrode sheet]

[0195] According to some embodiments of the present application, the method for preparing the negative electrode sheet is as follows:

[0196] (4) Dry mixing of materials: at room temperature, 93% to 97% by weight of active material graphite, 0.2% to 2.0% by weight of conductive agent carbon powder, and 0.2% to 2.0% by weight of dispersant sodium carboxymethyl cellulose are placed in a stirring container, and stirred to form a uniformly mixed dry powder;

[0197] (5) First stirring: adding deionized water to the stirring container of step (4) at room temperature and stirring to form a uniform slurry;

[0198] (6) Second stirring: At room temperature, add 1.5% to 3.0% of a binder by weight to the stirring container after treatment in step (5), and further stir to form a mixed slurry. The viscosity of the mixed slurry can be flexibly adjusted according to the amount of deionized water used. When deionized water needs to be added, add it in small amounts multiple times and stir thoroughly. For example, the present application chooses to control the viscosity to 3000 to 15000 Pa·s.

[0199] Then, the vacuum degassing device is turned on to perform vacuum degassing on the mixed slurry. For example, the vacuum degree of the vacuum degassing device can reach above -50KPa to obtain a uniform mixed slurry. The solid content of the mixed slurry is 40-60%.

[0200] (7) The mixed slurry obtained in step (6) is evenly coated on the copper foil current collector at a coating speed of 20 m / min and a coating mass of 120 g / 1540.25 mm 2 The oven temperature was set at 80°C. After drying in the oven, a cold press was further used to perform cold pressing at a certain pressure and speed. The cold pressing pressure was set at 30 tons and the cold pressing speed was 15 m / min to obtain the negative electrode sheet.

[0201] [Performance test of negative electrode]

[0202] According to some embodiments of the present application, the negative electrode sheet is tested for adhesion and cohesion, wherein the raw materials for the test come from the negative electrode sheet scraped off from the surface of the cold pressing roller of the cold press by a scraper during the cold pressing process in step (7) of preparing the negative electrode sheet.

[0203] (8) The bonding strength test of the negative electrode sheet was conducted using the following equipment: Zhongzhi Testing Tensile Tester (Model LXG2-LLCS-0009); the specific test process is as follows:

[0204] ① Use a blade to cut a negative electrode sample with a width of 30mm and a length of (90mm to 150mm), and stick the double-sided tape on the steel plate with a width of 20mm and a length of (90mm to 150mm).

[0205] ② Paste the negative electrode sample in step ① onto the double-sided tape, wherein the exposed outer side of the negative electrode sample is used as the test surface, and roll the test surface three times along the same direction with a roller with a width of 20 mm;

[0206] ③ Turn on the power of the tensile testing machine, fix the end of the steel plate without the negative electrode sheet with the lower clamp, ensure that the steel plate is placed vertically with the base, and the bottom of the steel plate is flush with the base, fold the negative electrode sheet pasted on the steel plate upwards, and fix it with the upper clamp.

[0207] ④ Start pre-tensioning, pre-tensioning about 5mm, then "clear" the "force" and "displacement" parameters. After the two parameters are reset to zero, click the start button to start the test, and then record the test results. Perform three sets of tests in parallel according to the above steps, calculate the average value N1, and the final bonding force = N1×50.

[0208] (9) The cohesion test of the negative electrode plate is carried out using the equipment: Zhongzhi Testing Tensile Tester (Model LXG2-LLCS-0009); the specific test process is as follows:

[0209] ⑤ Use a blade to cut the negative electrode sample with a width of 30mm × length of (90mm~150mm), and stick the double-sided tape on the steel plate with a width of 20mm × length of (90mm~150mm).

[0210] ⑥ Paste the negative electrode sample in step ⑤ onto the double-sided tape, wherein the exposed outer side of the negative electrode sample is used as the test surface, and a low-viscosity green tape with a width of 20 mm and a length greater than the length of the negative electrode sample by 80 mm to 200 mm is evenly pasted on the test surface, and a roller with a width of 20 mm is used to roll along the same direction of the test surface three times;

[0211] ⑦ Turn on the power of the tensile testing machine, fix the end of the steel plate without the negative electrode with the lower clamp, ensure that the steel plate is placed vertically with the base, and the bottom of the steel plate is flush with the base, fold the low-viscosity green glue upwards, and fix it with the upper clamp.

[0212] ⑧ Start pre-tensioning, pre-tensioning about 5mm, then "clear" the "force" and "displacement" parameters. After the two parameters are reset to zero, click the start button to start the test, and then record the test results. Perform three sets of tests in parallel according to the above steps, calculate the average value N2, and the final bonding force = N2×50.

[0213] The specific parameters and performance characteristics of the negative electrode plate are shown in Table 2; and the width of the negative electrode plate library in each embodiment and comparative example is 30 mm.

[0214] Table 2 Parameters of negative electrode

[0215]

[0216] It can be directly concluded from Table 2 that the bonding performance of the binder protected in this application is significantly better than that of SBR and CMC.

[0217] [Preparation of positive electrode sheet]

[0218] The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2, conductive agent Super-P, and binder polyvinylidene fluoride are stirred and dispersed in N-methylpyrrolidone in a mass ratio of 96:2:2 to prepare positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil, and after being compacted by a cold press, the positive electrode sheet is obtained.

[0219] [Preparation of electrolyte]

[0220] Lithium salt LiPF6 is added to a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 35:65, and the mixture is mixed evenly to obtain an electrolyte, wherein the molar concentration of LiPF6 in the electrolyte is 1 mol / L.

[0221] [Choice of isolation film]

[0222] A 12 μm thick polyethylene porous membrane was selected.

[0223] [Preparation of lithium-ion batteries]

[0224] According to some embodiments of the present application, the prepared negative electrode sheet, the isolation membrane and the positive electrode sheet are stacked in order, so that the isolation membrane is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, which is then inserted into a battery casing, and a lithium-ion battery is obtained through processes such as baking, liquid injection, standing, packaging, formation, and capacity division.

[0225] [Performance test of lithium-ion batteries]

[0226] (10) Battery DC pulse resistance (DCR) performance test:

[0227] The lithium-ion battery was fully charged at 0.5C and adjusted to 50% SOC by discharge. Then, the cell was pulsed at 4.0C for 30s at 25°C and the DC resistance DCR of the lithium-ion battery was recorded.

[0228] (11) Battery rate performance test:

[0229] The lithium-ion battery was charged and discharged at 25°C using 0.33C, 0.5C, 1C, 2C, and 3C, and the capacity retention rate at different rates was recorded.

[0230] (12) Test of lithium deposition on fully charged battery plates:

[0231] The lithium-ion battery was charged and discharged for 10 cycles at 3.0C at 25°C. After the battery was fully charged, it was disassembled and the interface was observed.

[0232] (13) Battery cycle performance test:

[0233] The lithium-ion battery was charged and discharged at 1C at 25°C, 45°C, and 60°C, respectively, and the capacity retention rate of the lithium-ion battery after 500 cycles was recorded.

[0234] (14) Battery storage performance test:

[0235] The lithium-ion battery was fully charged at 0.5C, and then stored at storage temperatures of 25°C, 45°C, and 60°C for 90 days, and the capacity retention rate of the lithium-ion battery after 90 days of storage was recorded.

[0236] The specific performance of lithium-ion batteries is shown in Table 3;

[0237] Table 3 Battery performance list

[0238]

[0239]

[0240] From the analysis of Tables 1 to 3, it can be seen that no obvious lithium deposition is observed in Comparative Examples 5 and 6, but the cycle performance of the battery is not as good as that of the present application, especially the cycle capacity retention rate at 60°C and the capacity retention rate after being placed for a certain period of time decay rapidly. This may be because the mass ratio between polymers A and B is not within the protection scope of the present application, and a conductive network cannot be effectively formed.

[0241] Comparative Examples 1 and 2 show that the negative electrode binder of the prior art still has an impact on the capacity retention performance, but the difference is not much compared with the present application. The more serious problem is that lithium precipitation is obvious, which can also be combined with Figure 5 see.

[0242] Comparative Examples 3 and 4 use only two monomers to form a polymer, which is used as a negative electrode binder. The battery cycle performance and capacity retention rate are not very ideal.

[0243] It can be seen from the above that the binder protected in this application improves the fast charging performance of lithium-ion batteries while also significantly reducing the probability of lithium plating.

[0244] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A binder, characterized in that: Comprising polymer A and polymer B in a mass ratio of (14-18):(2-6); The polymer A is formed by polymerizing monomer I, monomer II and monomer III; the polymer B comprises modified polyaniline; The structural formula of the monomer I is shown in Formula I: Among them, R 11 Contains one of hydrogen and C1-C5 alkyl, and M contains one of hydrogen or alkali metal cation; The structural formula of the monomer II is shown in Formula II: Among them, R 21 Contains one of hydrogen and C1-C5 alkyl; The structural formula of the monomer III is shown in Formula III: Among them, R 31 Contains one of hydrogen and C1-C5 alkyl.

2. The adhesive according to claim 1, characterized in that: The mass ratio of polymer A to polymer B satisfies: (15-17): (2-6), preferably (15-17): (3-5).

3. The adhesive according to claim 1, characterized in that: The binder further comprises a solvent; Preferably, the sum of the mass of the polymer A and the polymer B and the volume of the solvent satisfy: (1-10) kg / (80-100) L; Preferably, the solvent comprises water.

4. The adhesive according to any one of claims 1 to 3, characterized in that: The weight average molecular weight of the polymer A satisfies: 400,000 to 800,000, preferably 440,000 to 765,000.

5. The adhesive according to any one of claims 1 to 3, characterized in that: In the monomer I, R 11 Contains one of hydrogen or C1-C3 alkyl; Preferably, the monomer I comprises one or a combination of two or more of acrylic acid, methacrylic acid, ethacrylic acid, and lithium acrylate; Preferably, the monomer II comprises one or both of acrylonitrile and methacrylonitrile; Preferably, the monomer III comprises one or both of acrylamide and methacrylamide.

6. The adhesive according to any one of claims 1 to 3, characterized in that: Based on the total weight of the polymer A, the mass percentage of the monomer I is 50% to 70%, the mass percentage of the monomer II is 20% to 30%, and the mass percentage of the monomer III is 10% to 20%.

7. The adhesive according to any one of claims 1 to 3, characterized in that: The weight average molecular weight of the polymer B satisfies: 50,000 to 60,000, preferably 52,450 to 59,600.

8. The adhesive according to any one of claims 1 to 3, characterized in that: The polymer B comprises doped modified polyaniline; Preferably, the doped modified polyaniline comprises modifying polyaniline with a dopant, and the dopant comprises one or more of polystyrene sulfonic acid, polystyrene sulfonate, polyvinyl sulfonic acid, and polyvinyl sulfonate; Preferably, based on the total weight of the doped modified polyaniline, the mass percentage of the dopant is 5% to 20%.

9. The adhesive according to any one of claims 1 to 3, characterized in that: The performance of the binder at room temperature satisfies one or more of the following combinations: (1) Solid content is 4% to 10%, preferably 4.5% to 9.8%; (2) Viscosity is 10000 Pa·s to 20000 Pa·s, preferably 12500 Pa·s to 19750 Pa·s; (3) The electrical conductivity is 5 S / cm to 20 S / cm, preferably 6.5 S / cm to 18.6 S / cm.

10. A negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode membrane disposed on at least one surface of the negative electrode current collector, wherein the negative electrode membrane comprises a negative electrode active material, a conductive agent, a dispersant and the binder according to any one of claims 1 to 9.

11. The negative electrode plate according to claim 10, characterized in that: Based on the total weight of the negative electrode film, the mass percentage of the binder is 1.5% to 3.0%, preferably 1.8% to 2.5%.

12. The negative electrode sheet according to any one of claims 10 to 11, characterized in that: Based on the total weight of the negative electrode film, the mass percentage of the conductive agent is 0.2% to 2.0%, preferably 0.2% to 1.5%.

13. The negative electrode sheet according to any one of claims 10 to 11, characterized in that: Based on the total weight of the negative electrode membrane, the mass percentage of the dispersant is 0.2% to 2.0%, preferably 0.2% to 1.5%.

14. A battery cell, characterized in that: A negative electrode sheet comprising any one of claims 10 to 13.

15. A battery, characterized in that: Comprising the battery cell as claimed in claim 14.

16. An electrical device, characterized in that: It comprises the binder according to any one of claims 1 to 9, the negative electrode sheet according to any one of claims 10 to 13, the battery cell according to claim 14, or the battery according to claim 15.

Citation Information

Cited By

  • Composite binder, negative pole piece and preparation method of negative pole piece

    CN121610210A